Ischemia‐reperfusion injury of brain induces endothelial‐mesenchymal transition and vascular fibrosis via activating let‐7i/TGF‐βR1 double‐negative feedback loop. Issue 5 (10th April 2020) - Chen, Danqi; Li, Ling; Wang, Ying; Xu, Ruoting; Peng, Shunli; Zhou, Liang; Deng, Zhen
Abstract: Let‐7i modulates the physical function and inflammation in endothelial cells (ECs). However, whether the let‐7i of ECs involves in brain vasculature and ischemic stroke is unknown. Using inducible Cadherin5‐Cre lineage‐tracking mice, a loxp‐RNA‐sponge conditional knockdown of let‐7 in ECs‐ induced increase of transforming growth factor‐β receptor type 1 (TGF‐βR1), endothelial‐mesenchymal transition (endMT), vascular fibrosis, and opening of the brain‐blood barrier (BBB). By this lineage‐tracking mice, we found that ECs underwent endMT after transient middle cerebral artery occlusion (MCAO). Through specifically overexpressed let‐7i in ECs, we found that it reduced TGF‐βR1, endMT, and vascular fibrosis. Furthermore, this overexpression reduced the infarct volume and leakage of the BBB, and improved the neurological function. Further, the expression of let‐7i decreased after MCAO, but was reversed by antagonist of TGF‐βR1 or inhibition of Mek phosphorylation. And the inhibition of Mek attenuated the vascular fibrosis after MCAO. In summary, we concluded that ischemic stroke activates a let‐7i/TGF‐βR1 double‐negative feedback loop, thereby inducing endMT and vascular fibrosis. These results suggest that endMT is a potential target for the treatment of cerebral vascular fibrosis.